2014
DOI: 10.1007/s10689-014-9771-y
|View full text |Cite
|
Sign up to set email alerts
|

First-Line sunitinib in patients with renal cell carcinoma (RCC) in von Hippel–Lindau (VHL) disease: clinical outcome and patterns of radiological response

Abstract: rate of radiological response, patterns of responses in different organs, treatment-related toxicities. We performed a retrospective analysis of sunitinib therapy in genetically-confirmed VHL patients treated at our Institution for multifocal or advanced RCC. From February 2007 to July 2012, 14 VHL patients started first-line sunitinib for recurrent or progressing RCC, mean age 48 years (27-71). Nine patients achieved a partial RECIST response (64.3%); responses were noted not only in renal and hepatic lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Moreover, another international phase III trial for sporadic pancreatic neuroendocrine tumors demonstrated a relatively lower efficacy of sunitinib, PR of 9% and PFS of 11 months (10), whereas a phase II trial for sporadic pancreatic neuroendocrine tumors conducted in Japan reported a relatively favorable efficacy of sunitinib, PR of 50%, despite the small number of patients available for the analysis (n = 12) (22). The favorable outcome of our patient with PR maintenance from sunitinib therapy for nearly 5 years against RCC and pancreatic neuroendocrine tumor is in agreement with the results from these earlier reports (18)(19)(20)22) and suggests that sunitinib treatment is also effective in Japanese populations with VHL disease. Further prospective studies are required to elucidate whether patients with VHL disease have a better outcome from sunitinib treatment than patients with sporadic RCC or pancreatic neuroendocrine tumors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, another international phase III trial for sporadic pancreatic neuroendocrine tumors demonstrated a relatively lower efficacy of sunitinib, PR of 9% and PFS of 11 months (10), whereas a phase II trial for sporadic pancreatic neuroendocrine tumors conducted in Japan reported a relatively favorable efficacy of sunitinib, PR of 50%, despite the small number of patients available for the analysis (n = 12) (22). The favorable outcome of our patient with PR maintenance from sunitinib therapy for nearly 5 years against RCC and pancreatic neuroendocrine tumor is in agreement with the results from these earlier reports (18)(19)(20)22) and suggests that sunitinib treatment is also effective in Japanese populations with VHL disease. Further prospective studies are required to elucidate whether patients with VHL disease have a better outcome from sunitinib treatment than patients with sporadic RCC or pancreatic neuroendocrine tumors.…”
Section: Discussionsupporting
confidence: 89%
“…Kim et al reported that all four patients with VHL disease-associated metastatic RCC treated with sunitinib exhibited PR with a treatment duration of 19-51 months (19). More recently, Roma et al have shown in their retrospective analysis that 9 of 14 (64%) patients with recurrent or advanced RCC who received sunitinib treatment as a first-line therapy achieved PR, with a 2-year PFS of 71% (20). These studies, despite a relatively small number of patients analyzed, suggest that sunitinib treatment is even more effective in patients with VHL disease compared to those with sporadic RCC or pancreatic neuroendocrine tumor.…”
Section: Discussionmentioning
confidence: 99%
“…good for renal tumor lesions and little or no activity against hemangioblastomas) [13]. This pattern was also seen in a case report and a retrospective case review of VHL disease patients who had responses in mRCC tumors, but not other VHL lesions, after sunitinib [11, 14]. In addition, prolonged partial responses to sunitinib were reported for mRCC lesions in a series of four VHL disease cases [15].…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, it is conceivable that HIF2α inhiinhibitors has a modest, at best, effect on RCC lesions only. Published reports indicated a partial response of metastatic or locally advanced RCC in patients with VHL (36)(37)(38)(39). No medical therapy for HB exists so far; there has been no evidence of HB response to VEGF inhibitors in the patients with VHL treated for RCC.…”
Section: 9mentioning
confidence: 99%